2004
DOI: 10.1051/0004-6361:20047055
|View full text |Cite
|
Sign up to set email alerts
|

The oxygen abundance gradient in M 101: The reliability of thePmethod

Abstract: Abstract. We present the oxygen abundance determination for 90 H  regions in the inner parts of the grand design galaxy M 101. The abundances were derived employing the P method (Pilyugin 2001a). A comparison is made with previous determinations using another calibration and direct measurements of electron temperature to derive the oxygen abundance. The results show agreement with the abundances derived from the electron temperature method and also show that the older calibration is not as accurate as the P … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
15
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 18 publications
5
15
0
Order By: Relevance
“…However, if we take into account the position of the regions from Castellanos et al (2002) in the figure, it is clear that they lie closer to the gradient drawn by the PT05 calibration than that of KK04. This agrees with the results of Cedrés et al (2004) and López- Sánchez & Esteban (2010).…”
Section: The Metallicity Of Ngc 628supporting
confidence: 93%
See 3 more Smart Citations
“…However, if we take into account the position of the regions from Castellanos et al (2002) in the figure, it is clear that they lie closer to the gradient drawn by the PT05 calibration than that of KK04. This agrees with the results of Cedrés et al (2004) and López- Sánchez & Esteban (2010).…”
Section: The Metallicity Of Ngc 628supporting
confidence: 93%
“…Even if the PT05 method produces a larger dispersion than that for the KK04 method, the gradient and the metallicity values for single regions are closer to the direct-method results, as previously suggested in the literature (e.g. Cedrés et al 2004;or López-Sánchez & Esteban 2010). Two-dimensional contour models for the metallicity (and associated parameters) for both galaxies were created using the Delaunay triangulation.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…(1) Helfer et al (2003); (2) Sofue et al (1999); (3) Lu et al (1993); (4) Zimmer et al (2004); (5) Kamphuis & Briggs (1992); (6) Moustakas et al (2010); (7) Cedrés et al (2004). Foyle et al (2010), using a multiband analysis from H I to the far-UV for the grand design galaxies NGC 5194, NGC 682, and NGC 6946, found that there is no shock trigger, and that the spiral arms just reorganize the material from the disc, which will generate stars as a function of gas density, following a KennicuttSchmidt law, for example (Kennicutt 1998a).…”
Section: Introductionmentioning
confidence: 99%